PENGELOLAAN MODAL KERJA DALAM UPAYA MENJAGALIKUIDITAS DAN MENINGKATKAN PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan PT. Tiga Pilar Sejahtera Food, Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2012 – 2014) - Saputra, Aditya Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research was conducted to identify and explain about working capital management, liquidity level, and profitability level of a company. The object of this research is PT. Tiga Pilar Sejahtera Food, Tbk., a company engaged in food and beverage sector. This research uses source analysis, working capital usage, and financial ratio analysis that include liquidity, activity, and profitability ratio.This descriptive research uses quantitative approach to provide a clear picture on the issues, so it can contribute alternate solutions to the problems at PT. Tiga Pilar Sejahtera Food, Tbk in the period of 2012-2014The results of this study indicate that the working capital management is considered not good because the increase in working capital comes from long-term debt and not derived from the results of the company's operations as well as a decrease in inventory turnover and receivables resulting in decreased turnover of working capital. The liquidity level of the company was good and profitability level due to the increase of cost of goods sold and operating expenses in each year. Based on those problems, policies, programs, and actions to overcome the problems were prepared.Keyword: working capital, liquidity, activity, profitability, sources of working capital, usage of working capital